Microform, vídeo and electronic media Librarianship, de S. John Teague - Litto, Frederic M. (Revista de Biblioteconomia de Brasília, 1986)
TEAGUE, S. John. Microform, vídeo and electronic media Librarianship. London:Butterworths, 1985. 150 p.